(untitled) - DIAN NASTITI, SOFIE (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
This research is based on the appearance of phenomena rising the new beauty clinic which serve many products and services. Because of that, customers has consideration to choose the beauty clinic as their place for healty and skin care, the good service quality influence customers satisfaction. One of them is “Nanisa Beauty and Dental Clinic” in Sidoarjo which has complete care from hair until customer’s foot. Since the condition of a very dynamic product market, the traders work hard to win the strict competition. To get the customers, service quality is the main focus in this company. This research is to know the influence of service quality to customer satisfaction in “Nanisa Beauty & Dental Clinic” Sidoarjo. The research has been done for customers who came here minimum for twice. The technique of collecting samples is with accidental sampling. The analysis method used in the research is double linear regression and questionnaire as collecting respondent data then processed with the assistance of SPSS statistic program for Windows with 207 samples. The result of the research has shown that there is significant influence from variable of service quality that include tangible, responsiveness, assurance, empathy to customers satisfaction in “Nanisa Beauty & Dental Clinic” Sidoarjo is Based on the adjusted R2 value 41,6 % while the rest of 58,4% influenced by variables other than research. The tangible variable is dominant variable with grade tarithmetic is 6.713. Key Words : Service Quality, Customers Satisfaction